A PolSAR despeckling method based on Wishart gradient and anisotropic diffusion. Issue 3 (28th January 2021) - Wang, Hongmiao; Zeng, Liang; Zhang, Tao; Yin, Junjun; Yang, Jian
Abstract: The anisotropic diffusion filtering is a classical tool in image processing due to its simplicity and effectiveness. In this letter, we propose a new diffusion‐like filter based on the polarimetric synthetic aperture radar (PolSAR) ratio gradients. The PolSAR ratio gradients combine the information of different polarisation channels and describe the local directional changes in polarimetric characteristics. The proposed filter is then built by utilising the new gradients to derive the diffusion coefficients. The experimental results on synthetic data and real PolSAR images demonstrate the superiority and effectiveness of the new method.